Pengembangan Permainan Berlandaskan Nilai Karakter Keindonesiaan pada Siswa Sekolah Dasar - Permana, Erwin Putera; Wiguna, Frans Aditia; Rosalia, Novita Dewi (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
In the current era of globalization, science and technology are developing rapidly, so what happens in Indonesia. Concerns of Indonesian people as a pluralistic society have great potential to experience social conflict, currently proven. The SARA political conflict in the 2017 DKI Jakarta Regional Election case plus the political situation before and after the 2019 election is one of the proofs. Therefore education needs to be renewed. The renewal that can be done is the development of the game based on the Indonesian character development. In this research development researchers used two types of data analysis techniques, namely quantitative and qualitative data analysis techniques. Whereas the development research model chosen was the research and education development model developed by Borg and Gall with data collection techniques through observation, questionnaires and questionnaires. In conclusion, the game of Indonesian character values ​​needs to be applied to learning. This is evidenced from the results of the analysis that the implementation of the game at the elementary school level has a high level of validity and practicality. In addition, the play of Indonesian character values ​​can stimulate the enthusiasm and enthusiasm of students in understanding and applying Indonesian characters at the elementary school level and being able to answer the concerns of parents to children about the low moral values ​​due to sara and modern cultural issues.